(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the evolution and significance of postmodernism as a cultural and intellectual movement that emerged in the mid-20th century and challenged established norms and conventions in a variety of fields, including literature, art, architecture, philosophy, and social theory. By tracing the historical roots of postmodernism, the article examines key influences such as modernism, existentialism, and structuralism, and highlights how these frameworks contributed to the emergence of postmodern thought.